Effect of Anode Porosity and Temperature on the Performance and Lithium Plating During Fast‐Charging of Lithium‐Ion Cells. Issue 1 (12th November 2020) - Robertson, David C.; Flores, LeRoy; Dunlop, Alison R.; Trask, Stephen E.; Usseglio-Viretta, Francois L. E.; Colclasure, Andrew M.; Yang, Zhenzhen; Bloom, Ira
Abstract : Twenty‐four single‐layer ≈32 mAh pouch cells are tested to determine the effect of electrode porosity on lithium plating. Twelve cells contain a graphite electrode that is 26% porous, and 47% for the other twelve. The cells are cycled using a 6‐C charge and a C/2 discharge protocol at temperatures in the range of 20‐50 °C. A macro‐homogeneous electrochemical model and microstructure analysis tool set are used to help interpret experimental observations for the effect of anode porosity and ambient temperature on fast‐charging performance. Comparison between the two also highlights gaps in current theoretical understanding that need to be addressed. In post‐test examination, lithium plating is seen in all cells, regardless of porosity. Elevated temperature is shown to reduce the amount of lithium plating and improve initial fast‐charge capacity, but also changes the rate of other, less well‐understood degradation mechanisms. Apparent kinetic rate laws, At + Bt 1/2, where A and B are constants, can be fit to most of the capacity loss and resistance increase data. The relative magnitudes of A and B change with temperature and porosity. The capacity loss data at 50 °C from the high‐porosity cells are fit by a logistics rate law. Abstract : Severe salt depletion is predicted at/near the anode in this model in the low porosity case. It is not as severe in the high porosity one. Salt depletion may be one factor leading to lithium plating.